(3JGQjN GdadSaI ddeHJOFjf (B/s - (3cQe, jhSas ((3GdOeGe (B[(3GdSYhOjI(B]:s (3GdQjGV (B[(3GdSYhOjI(B]:s (3LOI (B[(3GdSYhOjI(B]:s (3ecJHI GdeJfHj,s, 2019)
(3gPG GdcJGH jbOe JGQjN GdadSaI ddeHJOFjf HCSdhH eNJUQ aj ZjQ ENdGd, heQcR aj ZjQ JYbjO, eSJYjfG HGdJGQjN hGdbUI dJhVjM eG ZeV ef GdCacGQ hJPdjd eG UYH ef GdBQGA hGdfXQjGJ(B. (3hEdi LGfH gPG, aGdcJGH YQV TGFb deTcdGJ GdadSaI, hHjGf HGdCOhGQ GdJj eQJ HgG NdGd GdMVGQGJ GdeNJdaI (B: (3GdbOjeI hGdhSWi hGdMOjKI MJi GdYUQ GdMGVQ, eeG jSeM dfG HGdEdeGe HGdCacGQ GdadSajI GdeNJdaI(B-(3efWbjI cGfJ Ce CNdGbjI, SjchdhLjI Ce ejJGajRjbjI(B-(3heMGhdI agegG aj SjGbgG GdJGQjNj(B.s
(3JUeje GdZdGa (B: (3CSGeI Wg(B.s
(3HHdjhLQGajI (B: (3UaMI (B291-298.s
Keywords: (3GdadSaIs -- (3JGQjNs -- (3OQGSI hJYdjes